Acute exercise increases circulating inflammatory markers in overweight and obese compared with lean subjects - Christiansen, Tore; Bruun, Jens M.; Paulsen, Søren K.; Ølholm, Jens; Overgaard, Kristian; Pedersen, Steen B.; Richelsen, Bjørn (European journal of applied physiology, 2013)
The primary aim of the present study was to investigate if overweight and obese compared to lean individuals displayed differences in levels of inflammatory markers in circulation, skeletal muscle (SM) and adipose tissue (AT) after acute exercise. Fifteen lean (BMI: 22.4 ± 2 kg/m 2 ) and 16 overweight or obese (BMI 31.8 ± 3 kg/m 2 ) individuals were included in the study. They completed 120 min of ergometer bicycling at 55–60 % of maximal heart rate. Blood samples were obtained at baseline (T = 0), after 60 (T = 60) and 120 min of exercise (T = 120), and analyzed using an ELISA method. SM and AT biopsies were obtained at T0 and T120, and mRNA expression was investigated using a Real-time RT-PCR method. Circulating IL-6, TNF-α, IL-8, and IL-15 all increased at T = 120 min ( p < 0.01). Circulating IL-6 and IL-15 increased in all subjects at T = 120 min ( p < 0.01), but only the increase of IL-6 was significantly higher in overweight and obese subjects ( p < 0.05), and was positively correlated with body fat percentage ( p < 0.01). Circulating IL-8 and TNF-α were increased in overweight and obese ( p < 0.05) but not in lean subjects. Acute exercise induced an increase in IL-6 mRNA expression in SM biopsies ( p < 0.05). IL-6 as well as adiponectin mRNA expression was increased in AT biopsies ( p < 0.05); however, no effect of body weight was found. The findings suggest that the systemic inflammatory response to acute exercise is different in lean compared to overweight and obese subjects, with a more pronounced increase in inflammatory markers (e.g., IL-6, IL-8, and TNF-α) in overweight and obese individuals.